Ecological and social poverty traps: Complex interactions moving toward sustainable development. (5th October 2022) - Yang, Zhenshan; Yang, Ding; Sun, Dongqi; Zhong, Linsheng
Abstract: Different types of poverty traps can reinforce each other, and consequently, multiple traps pose challenges for poverty alleviation, especially in rural areas. There remains a lack of understanding of social and ecological poverty traps and their relationship with one another. We considered the Selinco area in the Tibetan highlands of China and investigated social and ecological poverty, for an understanding of the poverty trap through the land‐human relationship lens. We found that ecological and social poverty differ between various townships due to their poor ecological and social environs. We affirmed reinforcing feedback between ecological and social poverty, and that the relative importance of social and ecological poverty differs at various thresholds. These results advance our understanding of different poverty traps and their feedback process. The findings inform the policy‐making process when addressing the land‐human relationship to improve ecosystem stability and promote social equity to foster sustainable development.